1986
DOI: 10.1111/j.1365-2559.1986.tb02481.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoglandular complexes of the colon: structure and distribution

Abstract: The structure and distribution of lymphoglandular complexes of the colon are described. The cellular composition of these complexes, as detailed by immunohistochemistry and electron microscopy, suggests that they are sites of antigen processing. Variations in structure and in the number of complexes that are found in certain colonic diseases are documented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
110
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(115 citation statements)
references
References 13 publications
5
110
0
Order By: Relevance
“…Thus, on the basis of these findings, we believe that misplacement of crypt epithelium into the submucosa of hyperplastic polyps may occur via a mechanism similar to that observed in adenomas with so-called pseudoinvasion. In fact, we agree with Sobin (12,14), who first suggested that misplacement of epithelium may occur secondary to tissue damage from torsion, or twisting, of the polyp followed by protrusion of glands through inherently weak regions of the muscularis mucosae, such as those that occur normally adjacent to lymphoid aggregates. Although none of the hyperplastic polyps in our study were pedunculated, it is possible that minor trauma may occur due to other factors, such as vigorous peristalsis or bulky intraluminal material.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, on the basis of these findings, we believe that misplacement of crypt epithelium into the submucosa of hyperplastic polyps may occur via a mechanism similar to that observed in adenomas with so-called pseudoinvasion. In fact, we agree with Sobin (12,14), who first suggested that misplacement of epithelium may occur secondary to tissue damage from torsion, or twisting, of the polyp followed by protrusion of glands through inherently weak regions of the muscularis mucosae, such as those that occur normally adjacent to lymphoid aggregates. Although none of the hyperplastic polyps in our study were pedunculated, it is possible that minor trauma may occur due to other factors, such as vigorous peristalsis or bulky intraluminal material.…”
Section: Discussionsupporting
confidence: 91%
“…[1][2][3][4] The comparable density obtained with acetic acid staining and with H&E histology in our study suggest that the latter method is reliable, reproducible, and permits to evaluate the lymphoid aggregate density as well as additional parameters in conditions of active inflammation also. A wide range of 'normal' densities (from 3 to 25 aggregates/cm 2 ) has been obtained in necropsy specimens, [1][2][3] whereas the data on 'normal' diameter are scarce, being limited to an approximate range between 0.5 and 2 mm.…”
Section: Discussionmentioning
confidence: 53%
“…Even their frequency in healthy individuals is obscure, and, since the pioneeristic study of Dukes and Bussey, 1 a wide range of values has been reported. 2,3 Although sporadic papers have described the lymphoid aggregate features in several large bowel diseases, 2,4-6 their pathogenic role in common colorectal diseases is largely unexplored. Nonetheless, a transmural distribution of lymphoid aggregates is considered a histological peculiarity of Crohn's disease, 7 and the clinical implementation of lymphoid aggregate analysis has been proposed, as they may be detected both on double-contrast barium enema 8 and on colonoscopy.…”
mentioning
confidence: 99%
“…Colonic patches are also very likely to be involved in the pathogenesis of IBD. Lymphoid follicles with an M cell-containing follicle-associated epithelium have been reported to be abundant in the human colon, although they are smaller in size than Peyer's patches of the small intestine (42,43). These findings suggest that colonic patches are a functional type of GALT for Ag uptake and presentation and for T and B cell interactions.…”
Section: Discussionmentioning
confidence: 95%